Comparative Analysis of Lower Limb Muscle Strength Based on Gender and Children Aged 10-12 Year at Muhammadiyah Elementary School 08 Dau - Wahyudi SW, M. Ricky; Atika Yulianti; Ali Multazam (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: The growth and development of children aged 0-12 years are individuals who experience a very rapid growth and development process. However, in this modern era, technological developments have resulted in children becoming very lazy and reluctant to do physical activity. This can affect the development of motor skills. Muscle strength is a crucial aspect in human physical development. Muscle strength, especially in the lower leg muscles, can be influenced by several factors such as age and gender. Objective: to determine the comparison of leg muscle strength based on gender and children aged 10-12 years at SD Muhammadiyah Malang. Method: The research used was cross-sectional by taking a sample of 116 respondents. Meanwhile, the test used uses a comparison test. Results: One way ANOVA test showed p-value = 0.79 (<0.05) which shows that there is no significant difference at the age level of 10, 11 and 12 years on leg muscle strength in children. And Mann Whitney p-value = 0.00 (<0.05) which shows that there are differences based on male and female gender. Conclusion: Comparative analysis of lower leg muscle strength based on gender and age 10-12 years at SD Muhammadiyah 08 Dau did not provide significant results regarding differences in lower leg muscle strength based on age 10, 11, 12 years. Meanwhile, there are differences in lower leg muscle strength based on gender.